2015
DOI: 10.1017/asr.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Grand Designs: Assessing the African Energy Security Implications of the Grand Inga Dam

Abstract: Abstract:In May 2013 the Democratic Republic of the Congo (DRC) announced that construction of the world’s largest hydroelectric project will begin in October 2015. Upon completion, according to the DRC, the project will bring electricity to half the African continent. With funding from South Africa, the World Bank, the African Development Bank, and others, the U.S.$80 billion Grand Inga Hydroelectric project will construct a 44,000 megawatt (MW) dam anchored to a new transmission network able to distribute el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Advocates of large hydro dams have often exaggerated the benefits of developing the Inga project, while the true risks of the project are neglected. However, it needs to be highlighted that a project of this scale may be overwhelming for the continent, due to several requirements that need to be fulfilled in order to realise its full completion [7,14]. To achieve a regional electricity project of this dimension, it calls for a further development of the cross-border transmission network from DRC to other regions of SSA [7].…”
Section: Discussionmentioning
confidence: 99%
“…Advocates of large hydro dams have often exaggerated the benefits of developing the Inga project, while the true risks of the project are neglected. However, it needs to be highlighted that a project of this scale may be overwhelming for the continent, due to several requirements that need to be fulfilled in order to realise its full completion [7,14]. To achieve a regional electricity project of this dimension, it calls for a further development of the cross-border transmission network from DRC to other regions of SSA [7].…”
Section: Discussionmentioning
confidence: 99%
“…Taken times 12 months in a year, the above amount leads to USD 16,800,000,000 that the hydro-electrical power could bring to the country. These figures do not account for industrial usages and are not far from the estimate of USD 14.8 billion annually quoted by Green et al (2015), differences stemming essentially from charged cost per kilowatt hour. Overall, estimates would not change significantly, even if considerations were made of figures produced by Amisi (2015).…”
Section: Congo and Its Tributaries: An Infallible Communication Netmentioning
confidence: 72%
“…With increased debts, partnerships to build Inga would require that DRC mutes, at least temporary, certain of its claims on the national sovereignty. Beyond economic consequences such as increased debts described here, Green et al () identified significant negative environmental consequences if a reservoir‐based design was used to build the dam itself; these negative ecological consequences included the emission of millions of tons of greenhouse gases, the risk of flooding, increased seismicity and earthquakes, fisheries losses, alterations to water quality, and disease epidemics. As indicated above, there are genuine claims over Congo water for other countries.…”
Section: Results and Perspectivesmentioning
confidence: 93%
See 1 more Smart Citation
“…The authors report numerous problems that resulted from the large dam in Mozambique: grandiose plans that have to be scaled back, goals that are never reached ("expanding regional productivity, enhancing the living conditions of the indigenous population, substantially increasing the number of Europeans in the Zambezi valley, and ending flooding") [32]. These findings are supported by a number of recent articles looking at large dam projects, both those that have been built and some that are now being touted as solving the energy access challenges in Africa [33][34][35]. While dams do hold the promise of dramatic increases in installed capacity, the Cahora Bassa is a stark reminder of what can go wrong and the major challenges of reaching the goal of greater access to electricity for the people living in these countries, as opposed to only mining and other industrial sectors.…”
Section: Beware Mega-projectsmentioning
confidence: 90%